2016
DOI: 10.1111/mam.12055
|View full text |Cite
|
Sign up to set email alerts
|

Biological matrices for sampling free‐ranging cetaceans and the implications of their use for reproductive endocrine monitoring

Abstract: Monitoring reproductive rates in wild cetaceans is a crucial step towards adequate management of their populations. Their reproductive hormone profiles can be of importance, especially when combined with behavioural or life history monitoring. Sampling biological matrices of wild, free‐ranging cetaceans can be a difficult task. The purposes of this review are: to describe briefly the different methods available for monitoring the reproductive endocrine parameters of wild and captive cetaceans, and to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…Profiling hormone concentrations in the tissues of walruses demonstrates that endocrine analyses are potentially useful indicators in determining reproductive states of this species. While this has been done in multiple species with many types of matrices [2,3], no studies using ovarian tissue of marine mammals for endocrine analyses were found in published literature. The ovarian tissues used in this study are unique in that they are the source location in which progesterone and estrogens are produced, rather than the more commonly sampled matrices used in endocrinology studies of marine mammals such as blood, blubber, and feces [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Profiling hormone concentrations in the tissues of walruses demonstrates that endocrine analyses are potentially useful indicators in determining reproductive states of this species. While this has been done in multiple species with many types of matrices [2,3], no studies using ovarian tissue of marine mammals for endocrine analyses were found in published literature. The ovarian tissues used in this study are unique in that they are the source location in which progesterone and estrogens are produced, rather than the more commonly sampled matrices used in endocrinology studies of marine mammals such as blood, blubber, and feces [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…While this has been done in multiple species with many types of matrices [2,3], no studies using ovarian tissue of marine mammals for endocrine analyses were found in published literature. The ovarian tissues used in this study are unique in that they are the source location in which progesterone and estrogens are produced, rather than the more commonly sampled matrices used in endocrinology studies of marine mammals such as blood, blubber, and feces [2,3]. This allowed the measurement of sex steroid hormones from the animal at the time of sampling and directly from the production site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress has been made at recovering and quantifying some of the hormones described above from alternative tissue types in cetaceans, particularly faecal samples, respiratory vapour (‘blow’), and biopsy dart samples of skin and blubber ( Rolland et al , 2005 ; Hunt et al , 2006 , 2014a ; Kellar et al , 2006 ; reviewed in Hunt et al , 2013 ; De Mello and de Oliveira, 2016 ) and most recently earwax plugs ( Trumble et al , 2013 ). For example, progestagens in faeces, blow and blubber are significantly elevated in pregnant females, while faecal glucocorticoids and mineralocorticoids have been shown to correlate with exposure to environmental stressors such as chronic ocean noise and fishing gear entanglement ( Rolland et al , 2005 ; Hunt et al , 2006 ; Hogg et al , 2009 ; Kellar et al , 2013 ; Burgess et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sampling exhaled breath or 'blow' from wild whales may therefore provide a more representative assessment of the health status of individuals because samples can be randomly taken from the population. From a single sample of whale blow, scientists may be able to collect respiratory bacteria, lipids, proteins, DNA and hormones (Hogg et al, 2005(Hogg et al, , 2009Schroeder et al, 2009;Acevedo-Whitehouse et al, 2010;Hunt et al, 2013Hunt et al, , 2014Thompson et al, 2014;Burgess et al, 2016;De Mello and De Oliveira, 2016;Raverty et al, 2017). This information is important for whale conservation, as it can be collected over time to help monitor the recovery of whale populations postwhaling.…”
Section: Introductionmentioning
confidence: 99%